Hold me tight [compact disc, unabridged] : seven conversations for a lifetime of love - Johnson, Susan M. (Brilliance Audiobooks, 2008)
Are you looking to enrich a healthy relationship, revitalize a tired one, or rescue one gone awry? Dr. Sue Johnson, developer of Emotionally Focused Couple Therapy, shares her program for creating stronger, more secure relationships. The message is simple: Forget about learning how to argue better, analyzing your early childhood, making grand romantic gestures, or experimenting with new sexual positions. Instead, get to the emotional underpinnings of your relationship by recognizing that you are emotionally attached to and dependent on your partner in much the same way that a child is on a parent for nurturing, soothing, and protection. Dr. Johnson teaches that the way to enhance or save a relationship is to be open, attuned, and responsive to each other and to reestablish emotional connection.